Economic and social consequences of the Serbo-Turkish war 1876–1878 for Kingdom of Serbia - Dymarski, Miroslaw (Balcanica Posnaniensia. Acta et studia, 2022)
The article is concerned with the analysis of economic costs and social consequences of the Serbo-Turkish war of 1876–1878, both in its direct aftermath and for the situation in the Kingdom of Serbia in the long term. The immediate financial consequences of the war with Turkey are analyzed and the author also considers the costs of war reparations, requisitions, supporting war refugees who had fled to Serbia, and compensations for Muslim owners for the land and real estate they lost as a result of the incorporation of Sanjak of Niš and part of Sanjak of Pirot. The costs of the war reflected the Serbian state’s financial politics having been harnessed to realize a singular objective: political expansion into the territories historically linked to Serbia as an integral part of the process of building the Serbian nation-state.